Aplikasi Peramalan Kurs Valuta Asing Rupiah per Dollar Amerika Serikat dengan Menggunakan Metode Box-Jenkins (ARIMA) - Helmi, Herlina (TINGKAP, 2011)
ABSTRACT For a multinational company foreign exchange is one of key variable in their day to day activity. The ability in managing their forex portfolio could help them to achieve a good performance. This research was applying The Box â€“ Jenkins Method in order to forecast USD to IDR fluctuation. Using this method we find that it is suitable to apply this method for forecasting USD vis a vis IDR fluctuation.Â  We find the USD-IDR fluctuation statistically significant following an ARMA (2,1) process but for forecasting purposes it is better to use ARMA (4,1) process since this process have better explanatory power. We recommend using higher data frequency such as daily or weekly data for a better forecasting result and for the applicability of this model to the real world. Kata Kunci: Kurs, nilai tukar, ARIMA Model, Time Series Forecasting